Risiko Investasi dalam Pembangunan Jalan Tol di Indonesia - Karsaman, Rudy Hermawan (Center for Research and Community Services ITB, 2007)
In accordance with an effort to increase economic development for the welfare of the society, the government of Republic of Indonesia plan to develop infrastructures, including toll road, in a big scale. On the contrary to the high investment potential, there are some risks arise and have to be faced by government and investors. These risks has to be taken into account in investment cal culation as a whole and managed very well since the beginning so that it can be anticipated as early as possible. Risk management is a well and systematic approach to manage these risk, started from risk identification and responses. In toll business, t here are so many risk have to be faced in every stage, from planning, construction until operation and maintenance stages, with the magnitude of very small to very big and probability occurrence from very rare to always happen. In this case, attitude toward this risk are accept, mitigate, transfer to other party, or avoid at all. Regional/Local government could participate in toll road development, either as part of regulator or investor, this might slightly change risk implication.